New phylogenetic hypotheses for the core Chlorophyta based on chloroplast sequence data - Fučíková, Karolina; Leliaert, Frederik; Cooper, Endymion D.; Škaloud, Pavel; D'Hondt, Sofie; De Clerck, Olivier; Gurgel, Carlos F. D.; Lewis, Louise A.; Lewis, Paul O.; Lopez-Bautista, Juan M.; Delwiche, Charles F.; Verbruggen, Heroen (Frontiers in Ecology and Evolution, 2014)
Phylogenetic relationships in the green algal phylum Chlorophyta have long been subject to debate, especially at higher taxonomic ranks (order, class). The relationships among three traditionally defined and well-studied classes, Chlorophyceae, Trebouxiophyceae, and Ulvophyceae are of particular interest, as these groups are species-rich and ecologically important worldwide. Different phylogenetic hypotheses have been proposed over the past two decades and the monophyly of the individual classes has been disputed on occasion. Our study seeks to test these hypotheses by combining high throughput sequencing data from the chloroplast genome with increased taxon sampling. Our results suggest that while many of the deep relationships are still problematic to resolve, the classes Trebouxiophyceae and Ulvophyceae are likely not monophyletic as currently defined. Our results also support relationships among several trebouxiophycean taxa that were previously unresolved. Finally, we propose that the common term for the grouping of the three classes, “UTC clade”, be replaced with the term “core Chlorophyta” for the well-supported clade containing Chlorophyceae, taxa belonging to Ulvophyceae and Trebouxiophyceae, and the classes Chlorodendrophyceae and Pedinophyceae.